Who was Thomas Alva Edison? - Frith, Margaret; O'Brien, John, 1953- (New York : Grosset & Dunlap, 2005)
An introduction to the life and accomplishments of Thomas Edison, America's most famous inventor.
Who was Thomas Alva Edison? -- Always curious -- Young inventor -- Tom and his "boys" -- His invention factory -- Turning on the light -- Making moving pictures -- Always inventing.
Includes bibliographical references (p. 106).
5.0
3-6
790L
Keywords: Edison, Thomas A., -- 1847-1931 -- Juvenile literature; Edison, Thomas A., -- 1847-1931.; Edison, Thomas A., -- 1847-1931.; Inventors; Engineers; Inventors -- Biography; Engineers -- Biography; Inventors -- Biography; Electrical engineers -- Biography